FINANCIAL CONTINGENCY PERFORMANCE ON COMPANY VALUE: (A STUDY OF TRADING COMPANIES ON THE INDONESIA STOCK EXCHANGE 2018-2022) - Fauziah, Siti; Haninun, Haninun; Habiburahman, Habiburahman (Journal of Management, Business and Social Sciences, 2024)
This study aims to examine the effect of financial performance on firm value with Intellectual Capital as a moderating variable. Financial performance is proxied by Return on Assets (ROA) and Return on Equity (ROE) as independent variables, while Intellectual Capital serves as the moderating variable, and firm value is the dependent variable for the period 2018–2022. The research adopts a quantitative approach using secondary panel data obtained from the Indonesia Stock Exchange (IDX) website, company websites, Yahoo Finance, and the Indonesian Central Statistics Agency. Data collection was conducted through literature study. The population consists of financial reports of trading companies, firm value, Intellectual Capital, Return on Assets (ROA), and Return on Equity (ROE). The research object is the financial data of trading companies listed on the Indonesia Stock Exchange during 2018–2022. The sampling technique applied is purposive sampling. Data were analyzed using multiple regression and Moderated Regression Analysis (MRA) with SPSS version 20. The findings reveal that Return on Assets (ROA) has a direct and significant effect on firm value. In contrast, Return on Equity (ROE) shows no direct effect on firm value. Furthermore, Intellectual Capital strengthens the relationship between Return on Assets (ROA) and firm value, but weakens the relationship between Return on Equity (ROE) and firm value in trading companies listed on the Indonesia Stock Exchange during 2018–2022.